Integrating landscape in regional development: A multidisciplinary approach to evaluation in Trentino planning policies, Italy. (September 2018) - Brunetta, Grazia; Monaco, Roberto; Salizzoni, Emma; Salvarani, Francesco
Highlights: An example of landscape integration into sector-focused policies. A multidisciplinary approach to evaluation for retail planning policies. An indicator matrix to assess landscape quality. A dynamic model to assess people mobility preferences among retail areas. Research outcomes were adopted by the local regulatory framework on retail planning. Abstract: The systematic integration of landscape dimension into general and sector-focused planning policies is one of the European Landscape Convention crucial points. This aspect is still poorly implemented in Italy, where landscape is often conceived as a field of action separate from the territorial context. The article presents the outcomes of a multidisciplinary research aimed at integrating landscape dimension into sector-focused policies, namely retail policies, in the Autonomous Province of Trento (Trentino-Alto Adige Region, Italy). The local government recently reformed its territorial retail development policies so as to comply with European reform regulations and with national decrees regulating the programming of services. It implemented the sector's liberalization, but it did not give up the territorial planning and the conservation of the landscape values. In this context, a research was developed to evaluate retail development scenarios, and, more specifically, the opportunity to plan a Gross Leasable Area of territorial relevance. Two methods were used: an indicator matrix to assess landscape quality and a mathematical model to assess population mobility preferences among retail structures. This integrated evaluation approach allowed to highlight both the "rights of the landscape" and those of potential buyers. The outcomes of the research have been recently adopted by the APT regulatory framework on retail planning. The evaluation process actually acted as a process of collective learning, supporting political decision-making.